Suppression of DC-link voltage unbalance in three-level neutral-point clamped converters. Issue 2 (January 2018) - Porru, Mario; Serpi, Alessandro; Marongiu, Ignazio; Damiano, Alfonso
Highlights: Two control approaches for DC-Link equalization of a three-level NPC are proposed. The Digital Scalar PWM is extended to a three-level NPC. The proposed control schemes are compared to the multilevel space vector PWM. DC-Link equalization is achieved successfully at any power factor. P-based NPC control minimizes voltage and current ripple on DC-Link capacitors. Abstract: Two different control approaches for suppressing DC-link voltage unbalance in Three-Level Neutral-Point Clamped Converters (NPCs) are presented in this paper. They both guarantee DC-link voltage equalization over any NPC operating conditions, i.e. when the NPC feeds or is supplied by the main AC grid at different active and/or reactive power rates. The proposed control approaches consist of either a hysteresis or a proportional regulator, each of which synthesizes the most suitable control action based on the actual DC-link voltage unbalance. Particularly, two different PWM techniques have been developed in order to achieve DC-link voltage equalization successfully, preserving NPC voltage and current waveforms at the same time. The performances achievable by means of both the proposed control approaches have been compared to each other through an extensive simulation study in order to highlight their most important advantages and drawbacks, as well as their effectiveness over any operating conditions. Particularly, both control approaches are validated in the Matlab-Simulink environment referring to DC-link voltage equalization of an NPC that represents the point of common coupling between a DC microgrid and the main AC grid.